Salt and freeze resistant and erosion resistant composite modified repair mortar and preparation method thereof
Patent Information
- Application Number
- CN202611268392.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]针对上述问题,本发明提供了一种耐盐冻抗冲刷的复合改性修补砂浆及其制备方法,该修补砂浆采用"物理阻隔-化学结合-结构增强"三重防护体系,能够同时解决盐冻破坏、氯离子侵蚀、界面粘结差、抗冲刷能力不足和绿色环保性差等问题
1)三重防护体系,耐盐冻性能优异。物理阻隔层:氟烷基硅烷改性可再分散乳胶粉纯膜水接触角可达130°以上,在砂浆内部成膜后可形成连续疏水网络,硬化砂浆表面水接触角最高可达124°,显著降低水分和盐溶液的侵入;化学结合层:煅烧钙铝类水滑石具有独特的层状结构和记忆效应,能够有效结合渗入砂浆内部的氯离子,生成稳定的弗里德尔盐(Friedel's salt),氯离子扩散系数较普通砂浆显著降低,最高降幅可达80%以上;结构缓冲层:空心玻璃微珠引入适量封闭微孔,能够缓冲冻融循环产生的膨胀压力,同时碳化粉煤灰优化了砂浆的孔径分布,减少了有害孔的数量。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a repair mortar and its preparation method. Background Technology
[0002] In marine environments, concrete structures are subjected to long-term chloride erosion from tides and sea fog, as well as the scouring effect of waves. In cold northern regions, the extensive use of de-icing salt in winter leads to severe salt-freezing damage to road concrete. Salt-freezing damage is a complex physicochemical coupling process: first, chloride ions penetrate into the concrete, reacting chemically with the material components and causing structural loosening; simultaneously, the salt solution lowers the freezing point of water, making freeze-thaw cycles more frequent. During temperature changes, the crystallization pressure and osmotic pressure generated within the material work together to accelerate the damage process. Existing research shows that, typically, C30-C40 grade concrete undergoes up to 40% decrease in compressive strength after 50 freeze-thaw cycles in a 5% NaCl solution, resulting in significant quality damage and structural deterioration.
[0003] CN117466579B discloses a polymer repair mortar for marine concrete and its preparation method. It adopts a two-component system of "dry powder mortar + composite modified polymer". The composite modified polymer forms a dense waterproof protective film on the mortar surface, which physically blocks the intrusion of moisture and chloride ions. However, relying solely on physical barriers, it lacks the ability to actively chemically bind chloride ions, and chloride ions will still slowly penetrate after long-term service.
[0004] CN110372303A discloses a salt-freezing and anti-corrosion mortar, a mortar preparation method, and a construction method. It adopts a single-component dry powder system, improves performance through the synergistic effect of multiple components, and introduces micro-closed air bubbles with an air-entraining agent to buffer freeze-thaw pressure. It utilizes a small amount of hydrotalcite-like structure naturally generated during cement hydration to solidify chloride ions. However, relying solely on the hydrotalcite-like structure naturally generated during cement hydration results in a limited content and uneven distribution, and the reduction in chloride ion diffusion coefficient is less than 50%.
[0005] CN114044664B discloses a rapid repair material for airport cement pavement that is resistant to freezing and salt freezing, and its preparation method. It employs a two-component rapid repair system of "powder + silica sol modified emulsion," and the composite cementitious system achieves rapid hardening with a compressive strength ≥25MPa in 2 hours. The silica sol modified emulsion forms a closed film structure within the matrix, improving waterproof performance. However, relying solely on physical waterproofing barriers, without active chloride ion binding and structural buffering mechanisms, the relative dynamic elastic modulus decreases to below 80% after 50 salt freezing cycles.
[0006] Existing salt-freezing repair mortars suffer from the following technical defects: 1. Limited effectiveness of a single protective mechanism: Most products only improve frost resistance by adding hydrophobic agents or air-entraining agents, lacking the ability to actively bind chloride ions and failing to fundamentally prevent chloride ions from corroding steel bars. 2. Poor interfacial bonding performance: Materials such as rapid-hardening sulfoaluminate cement have high shrinkage rates, easily causing cracking of the repair layer itself; and poor interfacial bonding performance with old concrete, easily leading to secondary defects. 3. Insufficient erosion resistance: Under the erosion of marine waves and vehicle tire wear, the repair layer surface is prone to peeling and sanding, resulting in a short service life. 4. Poor long-term durability: Ordinary redispersible latex powder has poor water resistance, and its performance deteriorates significantly after long-term immersion; the toughening effect of single fibers is limited, making it difficult to resist the repeated stress generated by salt-freezing cycles. 5. Poor green environmental protection: Existing products use a large amount of high-carbon emission materials such as cement, resulting in low utilization of industrial solid waste.
[0007] Therefore, developing a repair mortar that combines excellent salt and frost resistance, erosion resistance, high interfacial bond strength, long-term durability, and environmental friendliness is of great significance for improving the repair effect of marine environments and de-icing salt road concrete structures. Summary of the Invention
[0008] To address the aforementioned problems, this invention provides a salt-freezing and erosion-resistant composite modified repair mortar and its preparation method. This repair mortar adopts a triple protection system of "physical barrier-chemical bonding-structural reinforcement," which can simultaneously solve problems such as salt-freezing damage, chloride ion erosion, poor interfacial bonding, insufficient erosion resistance, and poor environmental friendliness.
[0009] To achieve the above objectives, the following technical solution is adopted: The composition of the salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is as follows by weight: 300-400 parts of composite cementitious material; 550-650 parts of modified aggregate; 25-40 parts of composite functional admixture; 120-150 parts of water; The composition of the composite cementitious material by weight percentage is as follows: 40%–50% of grade 42.5 rapid-hardening sulfoaluminate cement, 20%–30% of grade 42.5 ordinary silicate cement, 5%–10% of calcined calcium aluminum hydrotalcite, 15%–25% of carbonized fly ash, and 3%–5% of silica fume; The modified aggregate is composed of the following by weight percentage: 85%–90% quartz sand, 5%–10% surface-modified rubber powder, and 3%–5% hollow glass microspheres; The composition of the composite functional additive is as follows by weight percentage: 40%–50% fluoroalkylsilane modified redispersible latex powder, 15%–20% polycarboxylate-based high-efficiency water-reducing agent, 5%–10% composite retarder, 3%–5% defoamer, 2%–3% starch ether, and 15%–30% composite fiber; the composite fiber is a compound of polypropylene fiber and basalt fiber in a mass ratio of 2:(1–3), and the fiber length is 6–12 mm.
[0010] According to the above scheme, the preparation method of calcined calcium-aluminum hydrotalcite includes the following steps: Calcium-aluminum hydrotalcite with a Ca / Al molar ratio of 1.5:1 to 3:1 was calcined at 400 to 800°C for 2 to 4 hours, and after natural cooling, it was ground to a specific surface area of 400 to 600 m². 2 / kg. After calcination, hydrotalcite loses interlayer water and carbonate ions, forming a mixed metal oxide with a "memory effect," which can reabsorb anions and restore its layered structure.
[0011] According to the above scheme, the preparation method of the carbonized fly ash includes the following steps: Fly ash is carbonized for 24–48 hours under conditions of CO2 concentration of 15%–20%, temperature of 60–80℃, and pressure of 0.2–0.3 MPa, with a carbonization degree of not less than 80%. The carbonization degree is determined by a calcination method: the carbonized fly ash is dried to constant weight at 105℃, then calcined at 950℃ for 1 hour, and the carbonization degree is calculated based on the mass loss before and after calcination. During carbonization, free CaO and active calcium-containing glassy phase components in the fly ash react with CO2 to generate stable CaCO3, which fills the internal pores of the fly ash, improving its density and strength.
[0012] According to the above scheme, the quartz sand is continuously graded from 20 to 200 mesh, with a fineness modulus of 2.3 to 3.0. Continuously graded quartz sand can improve the density and wear resistance of mortar, and reduce the number of harmful pores.
[0013] According to the above scheme, the preparation method of the surface-modified rubber powder includes the following steps: Waste tire rubber powder is passed through a 40-80 mesh sieve and then surface-treated with silane coupling agent KH-550 at a temperature of 60-80℃ for 1-2 hours. The amount of silane coupling agent used is 1%-3% of the rubber powder mass. The surface-modified rubber powder exhibits significantly improved interfacial bonding performance with the cement matrix, effectively absorbing impact energy and enhancing the toughness and crack resistance of the mortar.
[0014] According to the above scheme, the hollow glass microspheres have a particle size of 10–100 μm and a bulk density of 0.15–0.25 g / cm³. 3The compressive strength is not less than 30MPa. Hollow glass microspheres can introduce an appropriate amount of closed micropores into the mortar, buffering the expansion pressure generated by freeze-thaw cycles, while reducing the density and thermal conductivity of the mortar.
[0015] According to the above scheme, the fluoroalkylsilane-modified redispersible latex powder is obtained by modifying ethylene-vinyl acetate copolymer latex powder with tridecafluorooctyltriethoxysilane. The amount of modifier is 2% to 5% of the latex powder mass, and the water contact angle of the modified latex powder is not less than 130°. The modification process includes the following steps: mixing ethylene-vinyl acetate copolymer latex powder and tridecafluorooctyltriethoxysilane in a certain proportion, and stirring in a high-speed mixer at a speed of 1000 to 1500 r / min for 8 to 12 minutes. The introduction of fluoroalkylsilane gives the latex powder excellent hydrophobicity and weather resistance after film formation, and can form a continuous hydrophobic network inside the mortar, significantly reducing the water absorption rate of the mortar.
[0016] According to the above scheme, the polycarboxylate-based high-efficiency water-reducing agent is a standard polycarboxylate-based water-reducing agent with a water reduction rate ≥25% and a solid content ≥40%; the defoamer is a polyether-based defoamer with a defoaming rate ≥90%; the starch ether is hydroxypropyl starch ether with a degree of substitution of 0.05 to 0.2 and a viscosity of 5000 to 20000 mPa. s.
[0017] According to the above scheme, the composite retarder is a mixture of tartaric acid and borax in a mass ratio of 1:(1-2). Tartaric acid can slow down the early hydration rate of cement, and borax can form a synergistic effect with tartaric acid through different retarding mechanisms, so as to achieve precise control of mortar setting time and avoid excessive early strength loss caused by a single retarder.
[0018] This invention also provides a method for preparing the above-mentioned salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar, comprising the following steps: The composite cementitious material, modified aggregate, and composite functional additives are put into a dry powder mixer and mixed evenly; water is added and mixing is continued to obtain a uniform mortar mixture.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) Triple protection system with excellent salt and freeze resistance. Physical barrier layer: Fluoroalkylsilane modified redispersible latex powder pure film water contact angle can reach over 130°. After film formation inside the mortar, it can form a continuous hydrophobic network. The water contact angle on the hardened mortar surface can reach up to 124°, significantly reducing the intrusion of water and salt solutions; Chemical bonding layer: Calcined calcium aluminum hydrotalcite has a unique layered structure and memory effect, which can effectively bind chloride ions that penetrate into the mortar to generate stable Friedel's salt. The chloride ion diffusion coefficient is significantly reduced compared to ordinary mortar, with a maximum reduction of over 80%; Structural buffer layer: Hollow glass microspheres introduce an appropriate amount of closed micropores, which can buffer the expansion pressure generated by freeze-thaw cycles. At the same time, carbonized fly ash optimizes the pore size distribution of the mortar and reduces the number of harmful pores.
[0020] 2) Composite toughening technology significantly improves erosion and impact resistance. The synergistic effect of surface-modified rubber powder and composite fibers significantly improves the toughness and crack resistance of the mortar, with impact strength increasing by up to 60% or more; the continuous gradation of quartz sand improves the density and wear resistance of the mortar, reducing wear loss by up to 60% under the action of wave erosion and vehicle tire wear.
[0021] 3) High interfacial bond strength and good volume stability. The composite cementitious material system combines rapid-hardening sulfoaluminate cement with ordinary silicate cement, achieving a balance between rapid early strength development and continuous later strength growth; redispersible latex powder improves the bonding performance between the mortar and the old concrete interface, with a maximum tensile bond strength of 3.6 MPa after 28 days, which is far superior to ordinary repair mortar; the addition of carbonized fly ash and silica fume reduces the shrinkage rate of the mortar, with a drying shrinkage rate of less than 0.08% after 28 days, effectively preventing cracking and hollowing of the repair layer.
[0022] 4) Green and environmentally friendly, with significant carbon reduction effects. It makes extensive use of industrial waste fly ash and waste tire rubber powder, reducing solid waste pollution. Through the pretreatment process of carbonized fly ash, CO2 is fixed. Material balance calculations show that approximately 6-10 kg of CO2 can be fixed per cubic meter of the repair mortar used in this invention. Simultaneously, it effectively disposes of large quantities of industrial solid waste such as fly ash and waste rubber powder, resulting in significant carbon reduction and resource utilization benefits. Detailed Implementation
[0023] The following embodiments further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0024] The preparation process of some of the raw materials used in the specific implementation is as follows: Calcinated calcium-aluminum hydrotalcite: Calcium-aluminum hydrotalcite with a Ca / Al molar ratio of 2:1 was calcined at 600℃ for 3 hours, and after natural cooling, it was ground to a specific surface area of 500 m².2 / kg. Carbonized fly ash: Grade I fly ash was carbonized for 36 hours under conditions of CO2 concentration of 18%, temperature of 70℃, and pressure of 0.25MPa. The degree of carbonization was determined to be 85% by calcination. Surface-modified rubber powder: Waste tire rubber powder was passed through a 60-mesh sieve and surface-treated with silane coupling agent KH-550. The amount of silane coupling agent was 2% of the mass of the rubber powder. The treatment temperature was 70℃ and the treatment time was 1.5 hours. Fluoroalkylsilane-modified redispersible latex powder: Ethylene-vinyl acetate copolymer latex powder and tridecafluorooctyltriethoxysilane were mixed at a mass ratio of 100:3 and stirred in a high-speed mixer at a speed of 1200r / min for 10 minutes to obtain modified latex powder with a water contact angle of 135°. Unless otherwise specified, all other raw materials were obtained commercially. The testing of each performance indicator in the specific implementation method strictly adopts the following national standards and prescribed methods: 2-hour compressive strength and 28-day compressive strength: GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". 28-day tensile bond strength: GB / T50728-2011 "Technical Specification for Safety Appraisal of Strengthening Materials for Engineering Structures". 28-day drying shrinkage: GB / T50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (contact method). Water absorption: GB / T50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (atmospheric pressure water absorption method). Water contact angle: Tested on the polished surface of hardened mortar specimens using the drop method in GB / T30693-2014 "Determination of Water Contact Angle of Plastic Films and Sheets". Chloride ion diffusion coefficient: GB / T50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (Rapid chloride ion migration coefficient method, RCM method). Salt-freezing cycle test: Referring to the test apparatus and evaluation system of the rapid freezing method in GB / T50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete", a 5% NaCl solution was used as the freeze-thaw medium for accelerated testing. Mass loss rate and relative dynamic modulus of elasticity were used as evaluation indicators. Impact strength: Appendix D of JC / T2537-2019 "Cement-based Repair Materials" (drop hammer impact method). Abrasion loss: Appendix E of JC / T2537-2019 "Cement-based Repair Materials" (grinding wheel abrasion method).
[0025] Example 1 The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is made from the following raw materials in parts by weight: 350 parts composite cementitious material, 600 parts modified aggregate, 32 parts composite functional admixture, and 135 parts water.
[0026] The composite cementitious material is composed of the following components by weight percentage: 45% rapid-hardening sulfoaluminate cement of grade 42.5, 25% ordinary silicate cement of grade 42.5, 8% calcined calcium aluminum hydrotalcite, 18% carbonized fly ash, and 4% silica fume.
[0027] The modified aggregate is composed of the following components by weight percentage: 88% quartz sand (20-200 mesh continuous gradation, fineness modulus 2.6), 8% surface-modified rubber powder (60 mesh), and 4% hollow glass microspheres (particle size 10-100 μm).
[0028] The composite functional additive is composed of the following components by weight percentage: 45% fluoroalkylsilane modified redispersible latex powder, 18% polycarboxylate-based high-efficiency water-reducing agent, 8% composite retarder (tartaric acid: borax = 1:1.5), 4% defoamer (polyether), 2% starch ether, and 23% composite fiber (polypropylene fiber: basalt fiber = 2:1, length 9mm).
[0029] Preparation method: Weigh each raw material according to the weight parts; put the composite cementitious material, modified aggregate and composite functional additive into a dry powder mixer and stir for 4 minutes until uniform; add water and continue stirring for 2.5 minutes to obtain a uniform mortar mixture.
[0030] Example 2 The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is made from the following raw materials in parts by weight: 320 parts composite cementitious material, 630 parts modified aggregate, 28 parts composite functional admixture, and 128 parts water.
[0031] The composite cementitious material is composed of the following components by weight percentage: 42.5 grade rapid-hardening sulfoaluminate cement 42%, 42.5 grade ordinary silicate cement 28%, calcined calcium aluminum hydrotalcite 6%, carbonized fly ash 21%, and silica fume 3%.
[0032] The modified aggregate is composed of the following components by weight percentage: 90% quartz sand (20-200 mesh continuous gradation, fineness modulus 2.4), 6% surface-modified rubber powder (40 mesh), and 4% hollow glass microspheres (particle size 10-100 μm).
[0033] The composite functional additive is composed of the following components by weight percentage: 42% fluoroalkylsilane modified redispersible latex powder, 17% polycarboxylate-based high-efficiency water-reducing agent, 7% composite retarder (tartaric acid: borax = 1:1), 4% defoamer (polyether), 3% starch ether, and 27% composite fiber (polypropylene fiber: basalt fiber = 2:1.5, length 6mm).
[0034] The preparation method is the same as in Example 1.
[0035] Example 3 The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is made from the following raw materials in parts by weight: 380 parts composite cementitious material, 570 parts modified aggregate, 36 parts composite functional admixture, and 142 parts water.
[0036] The composite cementitious material is composed of the following components by weight percentage: 48% rapid-hardening sulfoaluminate cement of grade 42.5, 22% ordinary silicate cement of grade 42.5, 9% calcined calcium aluminum hydrotalcite, 16% carbonized fly ash, and 5% silica fume.
[0037] The modified aggregate is composed of the following components by weight percentage: 86% quartz sand (20-200 mesh continuous gradation, fineness modulus 2.8), 10% surface-modified rubber powder (80 mesh), and 4% hollow glass microspheres (particle size 10-100 μm).
[0038] The composite functional additive is composed of the following components by weight percentage: 48% fluoroalkylsilane modified redispersible latex powder, 19% polycarboxylate-based high-efficiency water-reducing agent, 9% composite retarder (tartaric acid: borax = 1:2), 3% defoamer (polyether), 2% starch ether, and 19% composite fiber (polypropylene fiber: basalt fiber = 2:2, length 12mm).
[0039] The preparation method is the same as in Example 1.
[0040] Example 4 The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is made from the following raw materials in parts by weight: 300 parts composite cementitious material, 650 parts modified aggregate, 25 parts composite functional admixture, and 120 parts water.
[0041] The composite cementitious material is composed of the following components by weight percentage: 40% of grade 42.5 rapid-hardening sulfoaluminate cement, 28% of grade 42.5 ordinary silicate cement, 6% of calcined calcium aluminum hydrotalcite, 23% of carbonized fly ash, and 3% of silica fume.
[0042] The modified aggregate is composed of the following components by weight percentage: 90% quartz sand (20-200 mesh continuous gradation, fineness modulus 2.3), 5% surface-modified rubber powder (60 mesh), and 5% hollow glass microspheres (particle size 10-100 μm).
[0043] The composite functional additive is composed of the following components by weight percentage: 44% fluoroalkylsilane modified redispersible latex powder, 20% polycarboxylate-based high-efficiency water-reducing agent, 10% composite retarder (tartaric acid: borax = 1:1.2), 5% defoamer (polyether), 3% starch ether, and 18% composite fiber (polypropylene fiber: basalt fiber = 2:1.2, length 8mm).
[0044] The preparation method is the same as in Example 1.
[0045] Example 5 The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar is made from the following raw materials in parts by weight: 400 parts composite cementitious material, 550 parts modified aggregate, 40 parts composite functional admixture, and 150 parts water.
[0046] The composite cementitious material is composed of the following components by weight percentage: 50% of grade 42.5 rapid-hardening sulfoaluminate cement, 20% of grade 42.5 ordinary silicate cement, 10% of calcined calcium aluminum hydrotalcite, 15% of carbonized fly ash, and 5% of silica fume.
[0047] The modified aggregate is composed of the following components by weight percentage: 85% quartz sand (20-200 mesh continuous gradation, fineness modulus 3.0), 10% surface-modified rubber powder (60 mesh), and 5% hollow glass microspheres (particle size 10-100 μm).
[0048] The composite functional additive is composed of the following components by weight percentage: 50% fluoroalkylsilane modified redispersible latex powder, 15% polycarboxylate-based high-efficiency water-reducing agent, 5% composite retarder (tartaric acid: borax = 1:1.8), 3% defoamer (polyether), 2% starch ether, and 25% composite fiber (polypropylene fiber: basalt fiber = 2:2.5, length 10mm).
[0049] The preparation method is the same as in Example 1.
[0050] The performance of the repair mortars prepared in Examples 1-5 was tested, and the test results are shown in Table 1.
[0051] Table 1
[0052] The test results show that the repair mortars prepared in Examples 1-5 of this invention have significantly better performance indicators than the ordinary repair mortars in the comparative examples. The improvement is particularly evident in salt-freezing resistance, chloride ion penetration resistance, impact resistance, and abrasion resistance. After 50 salt-freezing cycles, the mass loss of Example 5 was only 0.9%, and the relative dynamic modulus of elasticity remained at 91.7%, while the mass loss of the comparative example was as high as 4.2%, and the relative dynamic modulus of elasticity was only 65.7%.
[0053] Comparative Example 1 Repeat Example 1, except that the fluoroalkylsilane-modified redispersible latex powder is replaced with an equal mass of unmodified ethylene-vinyl acetate copolymer latex powder; all other aspects remain unchanged.
[0054] Comparative Example 2 Repeat Example 1, except that the calcined calcium-aluminum hydrotalcite is replaced with uncalcined calcium-aluminum hydrotalcite with a Ca / Al molar ratio of 2:1; the rest remains unchanged.
[0055] Comparative Example 3 Repeat Example 1, except that the hollow glass microspheres are replaced with the same mass of quartz sand; everything else remains the same.
[0056] The performance of the repair mortars prepared in proportions 1-5 was tested, and the test results are shown in Table 2.
[0057] Table 2
[0058] After replacing the modified ordinary EVA latex powder with Comparative Example 1, the water contact angle of the mortar decreased significantly from 118° to 82°, and the water absorption rate increased from 2.1% to 4.3%, directly demonstrating that fluoroalkylsilane modification can form a continuous hydrophobic network inside the mortar, significantly reducing the intrusion ability of water and salt solutions. With the increase in water intrusion, the mass loss after 50 salt-freezing cycles increased to 2.6%, the relative dynamic elastic modulus decreased to 79.3%, and the chloride ion diffusion coefficient also increased due to the increased liquid phase transport channels, further confirming that hydrophobic barrier is the first core line of defense against salt-freezing.
[0059] After replacing Comparative Example 2 with uncalcined hydrotalcite, the physical properties such as water contact angle and water absorption rate remained basically unchanged, but the chloride ion diffusion coefficient increased from 1.4 × 10⁻⁶. - ¹²m² / s increased significantly to 4.2×10 - The ¹²m² / s directly demonstrates that the "memory effect" activated by calcination is the core mechanism of chloride ion chemical solidification. The uncalcined hydrotalcite has a stable interlayer structure and cannot actively adsorb and bind chloride ions; its physical adsorption capacity is limited. Increased chloride ion erosion further exacerbates salt-freezing damage, resulting in significant deterioration in mass loss and relative dynamic elastic modulus, confirming that the chemically bonded layer is a crucial defense against deep chloride ion damage.
[0060] In Comparative Example 3, replacing hollow glass microspheres with quartz sand slightly improved compressive strength (due to increased aggregate density), while the hydrophobicity and chloride ion binding indices remained largely unchanged. However, the mass loss after 50 salt-freeze cycles increased to 2.4%, and the relative dynamic elastic modulus decreased to 80.2%, directly demonstrating that closed micropores can effectively buffer the expansion pressure generated by freeze-thaw cycles and reduce structural damage during the salt-freeze process. Simultaneously, the impact strength decreased slightly, further confirming the buffering and absorption effect of the microporous structure on impact energy and supporting the structural reinforcement layer's effect on improving durability and toughness.
[0061] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A composite modified repair mortar resistant to salt freezing and erosion, characterized in that... The composition by weight is as follows: 300-400 parts of composite cementitious material; 550-650 parts of modified aggregate; 25-40 parts of composite functional admixture; 120-150 parts of water; The composition of the composite cementitious material by weight percentage is as follows: 40%–50% of grade 42.5 rapid-hardening sulfoaluminate cement, 20%–30% of grade 42.5 ordinary silicate cement, 5%–10% of calcined calcium aluminum hydrotalcite, 15%–25% of carbonized fly ash, and 3%–5% of silica fume; The modified aggregate is composed of the following by weight percentage: 85%–90% quartz sand, 5%–10% surface-modified rubber powder, and 3%–5% hollow glass microspheres; The composition of the composite functional additive is as follows by weight percentage: 40%–50% fluoroalkylsilane modified redispersible latex powder, 15%–20% polycarboxylate-based high-efficiency water-reducing agent, 5%–10% composite retarder, 3%–5% defoamer, 2%–3% starch ether, and 15%–30% composite fiber; the composite fiber is a compound of polypropylene fiber and basalt fiber in a mass ratio of 2:(1–3), and the fiber length is 6–12 mm.
2. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The preparation method of the calcined calcium-aluminum hydrotalcite includes the following steps: Calcium-aluminum hydrotalcite with a Ca / Al molar ratio of 1.5:1 to 3:1 was calcined at 400 to 800°C for 2 to 4 hours, and after natural cooling, it was ground to a specific surface area of 400 to 600 m². 2 / kg.
3. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The method for preparing the carbonized fly ash includes the following steps: Fly ash is carbonized for 24 to 48 hours under conditions of CO2 concentration of 15% to 20%, temperature of 60 to 80℃, and pressure of 0.2 to 0.3 MPa, with a carbonization degree of not less than 80%.
4. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The quartz sand is of continuous gradation of 20-200 mesh, with a fineness modulus of 2.3-3.
0.
5. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The preparation method of the surface-modified rubber powder includes the following steps: Waste tire rubber powder is passed through a 40-80 mesh sieve and surface-treated with silane coupling agent KH-550 at a temperature of 60-80℃ for 1-2 hours. The amount of silane coupling agent used is 1%-3% of the mass of the rubber powder.
6. The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The hollow glass microspheres have a particle size of 10–100 μm and a bulk density of 0.15–0.25 g / cm³. 3 The compressive strength is not less than 30MPa.
7. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The fluoroalkylsilane-modified redispersible latex powder is obtained by modifying ethylene-vinyl acetate copolymer latex powder with tridecafluorooctyltriethoxysilane. The amount of modifier is 2% to 5% of the latex powder mass, and the water contact angle of the modified latex powder is not less than 130°.
8. The salt-resistant, freeze-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The polycarboxylate-based high-efficiency water-reducing agent is a standard type with a water reduction rate ≥25% and a solid content ≥40%; the defoamer is a polyether-based defoamer with a defoaming rate ≥90%; the starch ether is hydroxypropyl starch ether with a degree of substitution of 0.05–0.2 and a viscosity of 5000–20000 mPa. s.
9. The salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar as described in claim 1, characterized in that... The composite retarder is a mixture of tartaric acid and borax in a mass ratio of 1:(1-2).
10. A method for preparing the salt-resistant, freeze-thaw-resistant, and erosion-resistant composite modified repair mortar according to any one of claims 1-9, characterized in that... Includes the following steps: The composite cementitious material, modified aggregate, and composite functional additives are put into a dry powder mixer and mixed evenly; water is added and mixing is continued to obtain a uniform mortar mixture.
Citation Information
Patent Citations
Salt scaling resistant anticorrosive mortar as well as preparation method and construction method of mortar
CN110372303A
Polymer repair mortar for marine concrete and method for preparing the same
CN117466579B